Factors that influence environmental pollution perception among residents in Taman Kota Masai, Pasir Gudang / Nurul Balkis Badariah Abdullah and Haifa Nadhrah Hairi - Abdullah, Nurul Balkis Badariah; Hairi, Haifa Nadhrah (2022)
The title of the study is Factors That Influence Environmental Pollution Perception Among Residents in Taman Kota Masai, Pasir Gudang. The objective of this study was to examine the level of knowledge of environmental pollution, to examine the relationship between knowledge, practice and community participation on environmental pollution and lastly to examine the most and the least factor that influences environmental pollution. In addition, this study was conducted in Taman Kota Masai, Pasir Gudang, Johor. The method used to complete this project is through convenience sampling to 200 respondents through online questionnaires. In this study, we have identified the factors that influence environmental pollution to the surrounding population. The results show that knowledge, practice and community participation are very important for environmental pollution factors.